Water and nutrient resources in the Northern Sierra Madre uplands a survey on farmers' perceptions under cloud uncertainties - Saliling, Willie Jones B. (2009)
This paper explored the perceptions of upland farmers in Northern Sierra Madre Mountain Range in Luzon about their resources, land use practices, aspirations and problems. The survey found out that important aspirations and problems in upland farming were related to soil, water, nutrients and climate nested in the biophysical and social domains. Land use practices were reflected of water and nutrient availability and perceived rainfall distribution. Farmers explained these dynamics incorporating their local knowledge and perceptions about changes in their environment. They had identified several indicators for soil quality and some local knowledge in predicting weather occurrences. The use of modern technologies (e.g. chemical fertilizers, new varieties) was evidently observed. Though these technologies brought productivity, it made upland farming susceptible and vulnerable to stress and shocks. This paper outlined some possible strategies for adaptation. In a short note, USM's role can be explored with particular reference to the institutions' expertise in industrial crops.
Keywords: Upland farming; Land use